Sensitivity of YAC to measure the light-component spectrum of primary cosmic rays at the 'knee' energies. (16th February 2015) - Zhai, L M; Huang, J; Chen, D; Shibata, M; Katayose, Y; Zhang, Ying; Liu, J S; Chen, Xu; Hu, X B; Lin, Y H
Abstract: A new air-shower core-detector array (YAC: Yangbajing air-shower Core-detector array) has been developed to measure the primary cosmic-ray composition at the 'knee' energies in Tibet, China, focusing mainly on the light components. The prototype experiment (YAC-I) consisting of 16 detectors has been constructed and operated at Yangbajing (4300 m a.s.l.) in Tibet since May 2009. YAC-I is installed in the Tibet-III AS array and operates together. In this paper, we performed a Monte Carlo simulation to check the sensitivity of the YAC-I+Tibet-III array to the cosmic-ray light component of cosmic rays around the knee energies, taking account of the observation conditions of the actual YAC-I+Tibet-III array. The selection of light component from others was made by use of an artificial neural network. The simulation shows that the light-component spectrum estimated by our methods can well reproduce the input ones within 10% error, and there will be about 30% systematic errors mostly induced by the primary and interaction models used. It is found that the full-scale YAC and the Tibet-III array is powerful to study the cosmic-ray composition, in particular, to obtain the energy spectra of protons and helium nuclei around the knee energies.